2018
DOI: 10.1186/s13104-018-3591-3
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal administration of cationic liposomes enhanced granulocyte–macrophage colony-stimulating factor expression and this expression is dispensable for mucosal adjuvant activity

Abstract: ObjectiveInfectious diseases remain a threat to human life. Vaccination against pathogenic microbes is a primary method of treatment as well as prevention of infectious diseases. Particularly mucosal vaccination is a promising approach to fight against most infectious diseases, because mucosal surfaces are a major point of entry for most pathogens. We recently developed an effective mucosal adjuvant of cationic liposomes composed of 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP) and 3β-[N-(N′,N′-dimethylamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…GM‐CSF also promotes IL‐6 secretion (Evans, Shultz, Dranoff, Fuller, & Kamdar, 1998), and accordingly IL‐6 levels were also elevated when cells were subjected to PBs. Both chemokines play a pivotal role in the initiation of a humoral response to antigenic proteins (Tada, Hidaka, Kiyono, Kunisawa, & Aramaki, 2018), and IL‐6 has been explored as a molecular adjuvant for mucosal vaccines (Rath et al, 2013; Su et al, 2008; Thompson & Staats, 2011). The observed cytokine release indicates the PB formulation's potential to enhance immunity and to exert an adjuvant effect, which is in agreement with the findings of Whitehead et al (2014) and Hofbauer et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…GM‐CSF also promotes IL‐6 secretion (Evans, Shultz, Dranoff, Fuller, & Kamdar, 1998), and accordingly IL‐6 levels were also elevated when cells were subjected to PBs. Both chemokines play a pivotal role in the initiation of a humoral response to antigenic proteins (Tada, Hidaka, Kiyono, Kunisawa, & Aramaki, 2018), and IL‐6 has been explored as a molecular adjuvant for mucosal vaccines (Rath et al, 2013; Su et al, 2008; Thompson & Staats, 2011). The observed cytokine release indicates the PB formulation's potential to enhance immunity and to exert an adjuvant effect, which is in agreement with the findings of Whitehead et al (2014) and Hofbauer et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the different cellular uptake mechanisms of cationic and anionic NPs might lead to different immune effects following pulmonary administration. Through animal experiments in mice, Tada et al ( 29 ) demonstrated that cationic liposomes induced higher antigen-specific antibody levels compared with anionic and neutral liposomes. Similarly, Fromen et al ( 30 ) reported that cationic NPs (~37 mV) conjugated with model antigen ovalbumin induced a higher level of antigen-specific IgG and local mucosal IgA in the plasma and bronchoalveolar lavage fluid (BALF) of mice after pulmonary immunization.…”
Section: Application Of Nps In Respiratory Systemsmentioning
confidence: 99%
“…Further, the obtained samples were incubated for 1 h at 4 • C, and the serum sample was collected after centrifugation at 1200× g for 30 min. The nasal wash (200 µL of cold D-PBS), vaginal wash (100 µL of cold D-PBS), and bronchoalveolar lavage fluid (1000 µL of cold D-PBS) were collected [16,31,32]. The samples were stored at −80 • C until use.…”
Section: Immunization and Sampling Schedule For The Assessment Of Pspa-specific Antibody Productionmentioning
confidence: 99%